REVITALISASI SUMBER DAYA MANUSIA MELALUI DIGITALISASI - Meida Rachmawati; Cecep Sukrisna (Journal of Social Sustainability Management, 2022)
This paper presents the revitalization of human resources through digitalization as part of the organization's management system. As a knife of analysis in solving problems using deductive research methods through literature study as a data collection tool. From the results of the descriptive analysis, it was found that the implementation of the revitalization of human resources through digitization is the main agenda in the current digital era